ANALISIS PENGARUH KUALITAS PELAYANAN DAN FASILITAS KESEHATAN TERHADAP KEPUASAN PASIEN PUSKESMAS - Th. Radito (Universitas Negeri Yogyakarta, 2014)
This study aimed to examine the effect of quality of service and health facilities owned by the health center (Puskesmas) to the patient's satisfaction. Puskesmas as the spearhead of health services in the community are expected to provide quality service and have adequate health facilities so as to increase patient satisfaction.This research was conducted at the Puskesmas Mantrijeron Jl. Panjaitan Mantrijeron 52 Yogyakarta. Puskesmas Mantrijeron chosen as the study site because it is a health center that organizes the quality of health services by government programs of Yogyakarta and by standards of the ISO (International Organization For Standardization) 9001: 2008.Subjects were patients who had treatment and are being treated at the Puskesmas Mantrijeron during the past year. Data collected in the form of primary data derived from the questionnaire which distributed to each respondent. Methods of data analysis using multiple regression.The results showed that the quality of care and health facilities are significantly affects the increase in patient satisfaction. However, from the regression results indicate that the quality of service and health facilities was only able to explain of 39.1% patient satisfaction. While the remaining 60.9% is influenced by other factors.